Peranan orang Cina dalam perkembangan ekonomi Kedah, 1909-1941 / Rozaini Ahmad - Rozaini , Ahmad (2018)
This dissertation discusses the significant roles of the Chinese in the development of Kedah is economy from 1909 until 1941. In Kedah, the role of Chinese could be seen clearly through their contribution in the agriculture, business, leasing, plantation and mining sector. The Chinese precense in the state of Kedah occurred before 1909. During that years, the migration of the Chinese to Kedah transpired in a small scale. Nevertheless, after British domination b in 1909, the arrival of Chinese from various tribes and dialects started to increase. Furthermore, the British influence and power in Kedah led to the expansion of Chinese influences and ultimately they were able to monopolize the economic activity. In effect, this situation had let to the deterioration of Malaysï¿½ position in the economic activity. Hence, the primary question of this dissertation is to examine the extent of the roles played by the Chinese in fostering the economy of Kedah. In addition, this study also aim to identify the type of economic sectors that had been monopolized by the Chinese and its impact on Kedahï¿½s development and local communities. The contributions and roles of the Chinese could be seen in economic activities including investment, trade and labour. This dissertation employs a qualitative research method. Therefore, this study is mainly based on the primary sources, chiefly the Kedah Annual Report, State Secretary Files, Colonial Office Records (CO 273, CO 717 and CO 716), British High Commission Office Files as well as government gazettes. These materials are obtained from The National Archive of Malaysia and National Archive of Kedah. Based on the data that had been analyzed, this study found that economic development in Kedah was clearly dominated and monopolized by the Chinese, especially in the rice sector, rubber plantation, business and tin mining. In the paddy sector, for instance, the Chinese domination could be seen clearly in manufacturing aspects which involves collecting, processing and marketing of paddy revenue, in which they were involved as investors, manufacturers, wholesaler and retailers. This domination was getting stronger and firmer as the Chinese also dominate expertise and technology in the economic sector of Kedah. Through this domination, the Chinese manufacturers are able to produce more revenue and thus generate the higher profits. The output of this revenue contributed to Kedahï¿½s domestic income. Nonetheless, the domination of Chinese in the economic sector had diminished the role and position of the Malays and they became the subject of oppression. The Chinese active involvement in the economic sector was due to the strong support from the British government itself that offered various economic opportunities to them through the approval of tenders and licenses in carrying out economic activities in Kedah. With this steady support, the dominance of Chinese in the economic sector was getting stronger and contributed to the revenue of the state.